(untitled) (Research, Society and Development, 2021)
The right to happiness has been of particular relevance in several countries, such as Japan, Bhutan and Nigeria, culminating in the affirmation of this right in their letters. Thus, the present work seeks to explore, through bibliographic review, the concept of happiness, aiming to demonstrate that this right translates into one of the dimensions of the dignity of the human person, which allows us to claim for its positivism in the Federal Constitution of 1988, as duty of the Brazilian State, however, the work also focuses on the concern between a fine line existing between the legitimate positivization of happiness and the nefarious “felicitocracy”.